Photocatalytic activity of Zn0-PEG nanoparticles for palm oil mill secondary effluent (POMSE) treatment - Hairom, Nur Hanis Hayati; Ismail, Nurul Hana; Abd Hadi, Nurul Aisyah; Abu Bakar Sidik, Dilaelyana; Mohammad, Abdul Wahab (Apple Academy Press, 2020)
Palm oil mill secondary effluent (POMSE) has a high color intensity, dissolve oxygen, turbidity, and an organic load of BOD which still not achieved the discharged requirement by the Department of Environment (DOE) and led to detrimental to the aquatic life. The photocatalytic degradation process is one of the promising methods in wastewater treatment due to its advantages. However, the study on PMSE treatment using the photocatalytic degradation process in the presence of ZnO-PEG nanoparticles (NPs) is still limited. Therefore, this study reports on the photocatalytic degradation of POMSE by using ZnO-PEG NPs. The ZnO-PEG NPs was characterized by using XRD and FTIR where the results show that there are no impurities present in the samples and presenting the nature and the chemical bonds of ZnO-PEG nanoparticle.